DETERMINING CONTEXTUAL FACTORS OF THE 2022 SNAP ELECTIONS IN THE REPUBLIC OF SERBIA - Simić, Savo (Political Review, 2023)
The goal of this research is to determine four key contextual political factors in shaping the political framework for holding snap parliamentary elections in 2022. Some of them belong to long-term processes, such as the decline of democracy and opposition contestation of election conditions, while others are the products of current political events, such as environmental protests, opposition boycotts of elections, and the war in Ukraine. As a central factor, we single out the absence of inter-party dialogue and opposition participation in the 2020 elections, which produced an almost one-party representative body and a lack of parliamentary pluralism. Simultaneously we observe continuous democratic erosion of the Republic of Serbia, which prevents the long-term consolidation of democratic institutions. By the second cause, we imply the electoral calculation of the ruling party in unifying the Belgrade local elections with the presidential and parliamentary elections to ensure electoral victory. Environmental protests in 2021, initiated after the adoption of disputed normative acts without public deliberation, stand out as the third factor. The fourth reason for new elections included the positioning of Serbia within the conflict between Russia and Ukraine, requiring a review of the general will of the citizens and the consensus of the leading political actors on the issue of Kosovo and Metohia.
Keywords: elections; Republic of Serbia; stabilocracy; political parties; electoral boycott; civil protests; geopolitical influence